Borrowing Agreement with the Czech National Bank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The last comprehensive discussion of reform of the international monetary system (IMS)-the set of official arrangements that regulate key dimensions of balance of payments-international reserves, exchange rates, current payments, and capital flows-was held nearly four decades ago. In light of repeated and costly international financial crises since then, it is timely to review the structure of the IMS to assess how it can be strengthened and made more resilient. At issue is the confluence of, on one side, an unprecedented build-up in global current account imbalances and volatile cross border capital flows, accompanied by a sharp build-up of international reserves, and on the other side, the concentration of those reserves in a few reserve currencies facing new challenges in maintaining fiscal and financial stability. As pre-crisis trends appear set to resume, this tension calls for examining their broader implications for the stability and efficiency of the current system. While the paper views the problems of the IMS through this prism in the tension between high reserve demand and narrow reserve supply, it also inevitably touches on all the components of the IMS-exchange rate arrangements, capital flows, and the global adjustment process. It should also be seen in the broader context of the Fund's recent work on IMS stability, which started with a paper focused on exchange rate arrangements last summer and will continue in coming months with another on capital flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agreement; Amount; Fund; PP; SDR; Czech Republic